Implementation of the Sidoarjo (Sipraja) People's Service System as Public Service Innovation in Grabagan Village Bones District - Muhammadiyah Sidoarjo; Salsa Rahma Anindya; Hendra Sukmana (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe and analyze the implementation of the Sidoarjo (Sipraja) Public Service System as a Public Service Innovation in Grabagan Village, Tulangan District. This research has used qualitative descriptive research. Sipraja Application administrator in the Grabagan Village Government. The results of this study indicate that the implementation of Sipraja as a public service innovation in the Grabagan Village Government can be assessed from several aspects, namely 1) (Communication) The lack of socialization carried out by village officials has an impact on the community who are still not familiar with the SIPRAJA application. word of mouth without official socialization 2) Resources a. (human resources) often face challenges such as stacking files and unequal distribution of tasks, not to mention if the application is wrong and blank, the administrator must help manage files manually. b. (financially) according to information from the Sipraja administrator at the Grabagan Village Government. There is no separate special allocation for the Garabagan Village Government in the Sipraja Application. c. (equipment) The Grabagan Village Government only has one administrative computer for the Sipraja application, so 2 administrators must use personal cellphones if indeed many people take care of letters through Sipraja and the internet which is less stable can cause delays and slowness in correspondence activities. 3) Disposition, Processing Sipraja applications can be divided into two parts. That is, the attitude and reaction of program implementers to the program or policy, and decision making when there is a problem with the Sipraja application. It also takes into account the time spent on manual processing more quickly.